VMware VCP-DCV (Updated for vSphere 7) - Gordon, Adam; Rodrick, Mike (Packt Publishing, 2024)
The course begins by introducing you to basic virtualization concepts and the integration of vSphere in the SDDC and cloud infrastructure. It then progresses to the core of ESXi host architecture, including installation and configuration. You'll learn to utilize the DCUI and Host Client for effective ESXi host configuration, and delve into creating and provisioning virtual machines, along with an understanding of VMware Tools. The course focuses on essential networking concepts, guiding you through network configuration files, Network Manager CLI, and Network Time Protocol setups. You'll gain practical skills in NFS server and client configurations, exploring vSphere networking and storage vocabulary, creating VMFS and NFS datastores, and understanding multipathing. The course wraps up with a deep dive into vSphere security, including SELinux management and firewalld configuration. You'll also learn about virtual machine management, CPU and memory concepts in a virtualized environment, creating a vSphere DRS cluster, vSphere HA architecture, and updates using vSphere Lifecycle Manager, rounding out a complete skill set for managing vSphere environments. What you will learn Manage virtual machines and VMware Tools Configure and manage vSphere networks Implement vSphere storage solutions Secure vSphere environments effectively Utilize vSphere for virtual machine management Deploy and manage vSphere HA and DRS clusters Audience This course is ideal for IT professionals and system administrators aiming to specialize in virtualization with VMware vSphere 7. Knowledge of basic virtualization and networking concepts is recommended. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Adam Gordon: Adam Gordon has 30+ years as an IT instructor in the private and public sectors. He holds more than 160 IT certifications. He has trained thousands of IT pros over the course of his career. He has over 160 professional and IT certifications. Mike Rodrick: Mike Rodrick, the host, has more than 15 years of IT instruction experience, including 10 years as a Microsoft Certified Trainer. Mike became an ITProTV Edutainer in 2014. Certifications: GIAC Security Essentials; Azure Fundamentals; Microsoft 365 Fundamentals; Cybersec First Responder; CompTIA ITF+, A+, Network+, Security+, Project+; MCP; MCT; MCDST; MCITP; MCTS; MCSA; MCSE; MCDBA; Certified Ethical Hacker; Certified Wireless Administrator; Certified Internet Web Professional.